Comparison of self-collected and healthcare worker-collected rectovaginal swabs for group B streptococcus detection in pregnancy using PCR with a commercial collection-enrichment device - Kukovica, Iva; Omahen, Neža; Klobučar, Nika; Bučar, Martina; Franko Rutar, Anita; Perme, Tina; Lučovnik, Miha; Jeverica, Samo (Frontiers in Microbiology, 2025)
IntroductionUniversal screening for the detection of group B streptococcus (GBS) colonization in pregnant women was recently introduced in Slovenia. The aim of our study was to determine whether self-collection of rectovaginal swabs is a valid alternative to collection by healthcare workers (HCWs).MethodsA prospective, multicenter study was conducted between June and November 2023. A total of 227 pregnant women (aged 20 to 44 years) from the University Medical Center Ljubljana (n = 136), the Novo mesto Community Health Center (n = 48) and the Trebnje Community Health Center (n = 43) were included. Two swabs were taken: swab A by the HCWs using standard semi-solid Amies transport medium (Meus; current standard) and swab B by the pregnant woman following visual instructions using a commercial LIM Broth (Copan). Swabs were inoculated onto ChromID Strepto B (STRB) agars directly and after overnight enrichment in LIM broth. The NeuMoDx GBS assay was performed from the enrichment broth. A self-assessment questionnaire was completed after sampling. Performance characteristics were calculated and compared between different diagnostics test algorithms using McNemar’s test for paired samples.ResultsOverall, GBS was detected in 18% (95% CI 13–23%; n = 40) of swabs A and 19% (95% CI 14–25%; n = 43) of swabs B. PCR was superior in both groups. In the group of swabs collected by HCWs, 4 (40 vs. 36; 11.1% difference; p = 0.046) and 3 (40 vs. 37; 8.1% difference; p = 0.083) additional positives were detected with PCR compared to direct and enrichment culture, respectively; in the group of self-collected swabs, 4 (43 vs. 39; 10.3% difference; p = 0.046) and 6 (43 vs. 36; 16.2% difference; p = 0.014) additional positives were detected with PCR compared to direct and enrichment culture, respectively. Self-collection showed a trend towards a higher diagnostic yield. PCR after enrichment from self-collected samples was found to be the most sensitive method overall. 58.5% (n = 124/212; 95% CI 52–65%) of women would prefer the swabs taken by HCWs.DiscussionSelf-collection of rectovaginal swabs during pregnancy is a good alternative to HCW-collected swabs. PCR from enrichment broth was better for the detection of GBS compared to enrichment culture. Majority of women preferred swabs taken by HCWs.